Development of 18 polymorphic microsatellite markers for Vinca minor (Apocynaceae) via 454 pyrosequencing1. (11th May 2015) - Moeller, Sina; Wöhrmann, Tina; Huettel, Bruno; Weising, Kurt
Abstract : Premise of the study: Polymorphic microsatellite markers were developed in Vinca minor (Apocynaceae) to evaluate the level of clonality, population structure, and genetic diversity of the species within its native and introduced range. Methods and Results: A total of 1371 microsatellites were found in 43, 565 reads from 454 pyrosequencing of genomic V. minor DNA. Additional microsatellite loci were mined from publicly available cDNA sequences. After several rounds of screening, 18 primer pairs flanking di‐, tri‐, or tetranucleotide repeats were identified that revealed high levels of genetic diversity in two native Italian populations, with two to 11 alleles per locus. Clonal growth predominated in two populations from the introduced range in Germany. Five loci successfully cross‐amplified in three additional Vinca species. Conclusions: The novel polymorphic microsatellite markers are promising tools for studying clonality and population genetics of V. minor and for assessing the historical origin of Central European populations.